Assessment of pathogenicity of community-acquired methicillin-resistant Staphylococcus aureus isolates in peritonitis-induced mice - Zulkiflee, Nur Izzatie (2019)
Staphylococcus aureus strain with distinct genetic backgrounds may exhibit different virulence in animal models as well as associations with different clinical outcomes. Methicillin-Resistant S. aureus (MRSA) is known to be more problematic as it cannot be treated with common antibiotics. Traditionally, MRSA infections have been limited to hospitals and predisposed immunecompromised individuals. Recently, MRSA infections have been reported to occur outside of hospital setting. There has been an alarming increase in the incidence of Community-Acquired MRSA (CA-MRSA) infections. CA-MRSA can be a serious threat to public health, which spreads in community. In addition, the present of Panton-Valentine Leucocidin (PVL), pore-forming gene, has also been reported to be epidemiologically associated with CA-MRSA and may cause aggressive infections. Peritonitis is one of the results of S. aureus infection which caused potentially fatal inflammation of the peritoneum. S. aureus contributed for the greatest number of positive peritonitis cultures from patients with continuous ambulatory peritoneal dialysis and end-stage renal disease. Since the presence of CA-MRSA is continuously emerging, it is important to continue monitoring the distribution pattern and the pathogenic status of CA-MRSA in the community. In this study, the pathogenicity of CAMRSA isolates were assessed using in vivo model of peritonitis with comparison to a clinical isolate, ATCC 700699 MRSA (ATCC-MRSA). Two different CA-MRSA isolates (CA-MRSA1 and CA-MRSA2) were previously isolated from a healthy population were studied. Mice were assigned into 4 groups and intraperitoneally injected with 200 μl of 109 CFU/ml of ATCCMRSA, CA-MRSA1 and CA-MRSA2, respectively. Control group was injected with sterile DPBS. After inoculation, mice were observed twice daily until 72 hours post-infection and any distress signs were recorded. Mice were euthanized at 72 hours post-inoculation or had severe symptoms. Interested organs and peritoneal lavage were collected for bacterial load and histopathological analysis. All mice inoculated with MRSA showed clear signs of illness and developed symptoms of peritonitis (p<0.001). In addition, CAMRSA caused significant mortality rate and higher Peritonitis Severity Scoring (PSS) scores compared to un-infected mice, but comparable to reference isolate, ATCC-MRSA, with 80% and 100% of mortality recorded in CA-MRSA2 and CA-MRSA1, respectively. There is no significant different in mortality rate between CA-MRSA and ATCC-MRSA-infected mice. Bacterial count in liver, lung and spleen tissues isolated from CA-MRSA-infected mice were comparable to ATCC-MRSA group. Although it was not statistically different, CA-MRSA2 showed slightly higher bacterial counts compared to CA-MRSA1 and ATCC-MRSA in culture samples. In addition, histopathological comparison had showed mild increase in various indicators including inflammation, necrosis, edema, and haemorrhage, in tissue samples isolated from all MRSAinfected groups. Tissues isolated from CA-MRSA- and ATCC-MRSA-infected mice showed consistent histopathological scores. Abscess was only observed in CA-MRSA2 tissues samples. These results indicate that nasal carriage CAMRA isolated from a healthy population has potential to cause peritonitis, with comparable severity as clinical isolate, ATCC-MRSA. Together, informations obtained from this study provide new insight on the virulence status of MRSA nasal carriage isolates. Without appropriate intervention, CA-MRSA is likely to be a continuous threat to public health for the foreseeable future. Thus, it is important to ensure consistent practices are adopted towards early diagnosis, appropriate intervention and widespread surveillance to increase awareness that needed in terms of information or education on the risks, management and treatment of MRSA.